Respuesta :

First, you need to factor the function.  You can do this by finding a pair of numbers whose product is equal to the c term (-6) and whose sum is equal to the b term (-5).  These numbers are -6 and 1 (-6*1=-6, -6+1=5).  The factored expression takes the form:

(x+1)(x-6)=0

The zeroes can be found by flipping the signs in the parentheses.  The zeroes are equal to each number.

The zeroes are -1 and 6.

Hope this helps!!

Answer:

The zeros of F(x)  are -1 and 6

Step-by-step explanation:

It is given a polynomial

F(x) = x² - 5x - 6

To find the zeros of polynomial

F(x ) = x² - 5x - 6

Using splitting method

F(x ) = x² - 5x - 6 = F(x ) = x² + x - 6x - 6

 = x( x + 1) - 6 (x + 1)

= (x + 1)(x - 6)

Therefore the zeros of F(x)  are -1 and 6